2019
DOI: 10.2217/fmb-2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Verapamil in Rifampicin Activity Against Mycobacterium Tuberculosis

Abstract: Aim: To evaluate modulatory effect of verapamil (VP) in rifampicin (RIF) activity and its effect in efflux pumps (EPs) transcript levels in Mycobacterium tuberculosis. Materials & methods: RIF and VP minimal inhibitory concentration, combinatory effect and detection of mutations were determined in 16 isolates. EPs transcript levels were determined in four isolates by real-time PCR after exposure to drugs. Results: VP showed good combinatory effect among RIF-resistant isolates. This effect was also observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…1 to 3). All M. tuberculosis strains (although at a milder response for H 37 Rv) responded to stress caused by RIF through a general increase of EP transcript levels, similarly to results reported in a previous study (4). Relative transcript levels of Rv2942 and Rv1458c were not detected in H 37 Rv in any exposure condition.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…1 to 3). All M. tuberculosis strains (although at a milder response for H 37 Rv) responded to stress caused by RIF through a general increase of EP transcript levels, similarly to results reported in a previous study (4). Relative transcript levels of Rv2942 and Rv1458c were not detected in H 37 Rv in any exposure condition.…”
supporting
confidence: 86%
“…The emergence of anti-TB-drug-resistant M. tuberculosis strains highlights the need for new strategies to deal with TB worldwide. One particular strategy for future therapy is the use of efflux pump inhibitors (EPIs) added to anti-TB drugs (3,4).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Gupta et al also suggested that administration of verapamil together with bedaquiline reduces the bacterial load in M.tb infected mice and therefore calcium efflux blockers can be explored as adjuncts in TB therapy (93). After this pioneering work, many follow up studies also confirmed the protective role of verapamil in TB therapy (94)(95)(96). These studies demonstrated other mechanisms of protection conferred by verapamil such as by increasing the bioavailability of bedaquiline (94) and by disturbing the mycobacterial membrane energetics (95).…”
Section: Verapamilmentioning
confidence: 98%